2019
DOI: 10.31480/2330-4871/103
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Laryngeal Mask Airway-Related Hiccup: An Overview

Abstract: Hiccup is an involuntary contraction of the diaphragm and intercostal muscles resulting in sudden inspiration and closure of the glottis. The presence of hiccup in the perioperative period can be a challenging problem. Sudden movements of the patient from hiccups can interfere preoperative diagnostic procedures, intraoperative hiccup may delay the beginning of surgery, interfere with the surgical process, and affect intraoperative monitoring, and postoperative hiccup may affect would healing and hemodynamic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
3
1
Order By: Relevance
“…Hiccups can be triggered by stimulation of the vagus nerve or phrenic nerve, with the vagus nerve innervating the pharynx and upper esophagus. Previous studies have indicated that LMA insertion can stimulate the hypopharynx and induce hiccups, with reported incidences ranging from 3% to 11% [12,13]. However, in our study, only one patient experienced hiccups after LMA insertion, while five patients experienced hiccups during or after the bolus administration of remimazolam.…”
Section: Discussioncontrasting
confidence: 76%
“…Hiccups can be triggered by stimulation of the vagus nerve or phrenic nerve, with the vagus nerve innervating the pharynx and upper esophagus. Previous studies have indicated that LMA insertion can stimulate the hypopharynx and induce hiccups, with reported incidences ranging from 3% to 11% [12,13]. However, in our study, only one patient experienced hiccups after LMA insertion, while five patients experienced hiccups during or after the bolus administration of remimazolam.…”
Section: Discussioncontrasting
confidence: 76%
“…An inadvertent gastric insufflation during poor bag-mask ventilation technique or other patient-related factors, and prior diagnosis of gastroesophageal reflux disease may also present with intraoperative hiccups and are reported in about 4.5–9.5% of the patients. [ 5 ] LMA insertion has been claimed to inhibit hiccups[ 6 ] as well as implicated as a cause for this,[ 5 7 ] with an overall incidence of 5% that differed with the type of induction agent used intraoperatively. [ 5 ]…”
mentioning
confidence: 99%
“…[ 5 ] LMA insertion has been claimed to inhibit hiccups[ 6 ] as well as implicated as a cause for this,[ 5 7 ] with an overall incidence of 5% that differed with the type of induction agent used intraoperatively. [ 5 ]…”
mentioning
confidence: 99%
See 1 more Smart Citation